PENGARUH INFRASTRUKTUR DAN VARIASI SATWA TERHADAP MINAT KUNJUNG KEMBALI MASYARAKAT KABUPATEN GARUT PADA TAMAN SATWA CIKEMBULAN KADUNGORA GARUT - Lukmanul Hakim, Aditya; Hermina, Tinneke; Rawati Suganda, Fitrin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Ecotourism is a strategic sector in developing sustainable destinations that prioritize environmental conservation and education. Cikembulan Zoo, located in Garut Regency, is one of the educational tourism locations that offers recreational and learning experiences for the community. However, the dynamics of the number of visits show fluctuations, which require an evaluation of the determinants of visitor loyalty. This study aims to analyze the contribution of infrastructure and animal diversity to the intention of repeat visits by the Garut Regency community to Cikembulan Zoo in Kadungora District. The quantitative method used is the Structural Equation Modeling approach based on Partial Least Square (SEM-PLS). Data were obtained through questionnaires and analyzed using SmartPLS software. The results of the analysis show that infrastructure has a significant positive effect on the intention to revisit with a coefficient value of 0.649. Meanwhile, animal variation also contributes positively with a coefficient of 0.325. The coefficient of determination (R²) value of 0.934 indicates that the two independent variables are simultaneously able to explain 93.4% of the variation in the intention to revisit.